Potential and limitations of innovative housing solutions in planning for degrowth: the case of Vienna. Issue 4 (3rd April 2022) - Cucca, Roberta; Friesenecker, Michael
ABSTRACT: Limiting socio-spatial inequalities can be considered a decisive goal for a degrowth agenda. At different territorial scales, planning and housing policies have been crucial to achieve this goal, in terms of both reaching high environmental standards and framing the social reproduction of inequality. This article focuses on the implications, in terms of socio-spatial inequalities, of innovative housing solutions oriented to a degrowth agenda. It aims to answer to the following research questions: what are the socio-spatial implications of the most common innovative housing solutions that can best fulfil the degrowth principles/vision? How is it possible to ensure socio-spatial justice in housing projects inspired by a degrowth narrative? By analysing two cases of housing innovation in Vienna (qualitative analysis), we argue that many innovative housing projects, characterised by a degrowth narrative when it comes to the development of ecological and social practises, today show high level of elitism reproducing socio-spatial inequalities. However, we also argue that the role of local authorities can play a central role in up-scaling these housing innovations by ensuring higher level of inclusiveness.